Answer:
72.3 - 39.1 = 4tens - 7ones + 2tenth
Step-by-step explanation:
Give the expression 72.3 + (-39.1)
opening the parenthesis:
= 72.3 + (-39.1)
= 72.3 - 39.1
Breaking the decimal values into place values
72.3 = 7tens + 2units + 3tenth
72.3 = 7(10)+2(1)+3(1/10)
72.3 =70+2+0.3
Similarly for 39.1
39.1 = 3tens + 9units + 1tenth
39.1 = 3(10)+9(1)+1(1/10)
39.1 =30+9+0.1
72.3 - 39.1 = 70+2+0.3 - (30+9+0.1)
72.3 - 39.1 = 70+2+0.3 - 30-9-0.1
72.3 - 39.1 = 70-30+2-9+0.3-0.1
72.3 - 39.1 = 40 - 7 +0.2
72.3 - 39.1 = 4tens - 7ones + 2tenth
Answer:
7
Step-by-step explanation:
it's a rectangle of area 2*4=8 minus a triangle of area 1*2/2=1 so 8 - 1 = 7
Answer:
1 + 12
Step-by-step explanation:
Let's do this one step by step!
We are going to make sure that we pay attention to the part in the parenthesis first!
Let's multiply -2x with -6 first.
Equation:
4+(-3)-2x(-6)
We do not need to parenthesis around the -3 because a negative cancels out a positive. So, no matter what you would have to subtract.
4 - 3 + 12x
And we get a positive 12 because both numbers that were being multiplied were negative.
Now let's combine common terms.
1 + 12x
This is your answer! I hope this helped!